Galerie Vega - Manette Repriels. (Liège : Galerie Vega)
Beuys ; Cadere ; Gilbert & George ; Graham, Dan ; Leisgen, B. et M. ; Mangold ; Matta Clark, G. ; Nyst, J.L. ; Panamarenko ; Fulton, H. ; Tuttle, R. ; Zaza, M. ; Baldessari ; Broodthaers ; Dujourie, L. ; Paik, Nam June ; Oppenheim, D.
boek